PERAN MANAJEMEN SDM DAN KEUANGAN DALAM MENINGKATKAN MUTU PENDIDIKAN ISLAM - Ach. Aldi Rofiqi; Achmad Muhlis (Jurnal Manajemen Pendidikan, 2026)
Objective; Improving the quality of Islamic education requires professional, effective, and oriented institutional governance based on Islamic values. This research aims to analyze the role of human resource management (HR), financial management, and the integration of both in supporting the improvement of the quality and accountability of Islamic educational institutions. The research uses a qualitative approach with the library research method. Data is collected from various sources, including books, scientific journal articles, laws and regulations, and relevant documents, then analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that human resource management based on the values of trust, justice, responsibility, and professionalism contributes to improving the competence and performance of educators and education personnel. On the other hand, financial management that applies the principles of transparency, accountability, effectiveness, and efficiency is able to ensure the sustainability of educational programs and optimize the use of resources. The integration of HR and financial management through strategic planning, needs-based budgeting, human resource capacity development, and an integrated supervision system has been proven to strengthen the quality of educational services, increase accountability for institutional management, build public trust, and strengthen the competitiveness of Islamic educational institutions.